Rational Use of Drugs in Patients with Schizophrenia at Inpatient Installation of Dr. Soeharto Heerdjan Hospital Jakarta, Indonesia - Suriyati Hutauruk; Wawan Ridwan; Galianti Prihandayani; Rusti Winarni; Eko Heppy Purwanto (Universitas Muhammadiyah Yogyakarta, 2024)
Schizophrenia is one of the mental health diseases in the inpatient department of Dr. Soeharto Heerdjan Hospital. Prescribing for Schizophrenia patients must be the right drug, the right patient, the right diagnosis, the right dose, and the right frequency of drug administration. This study aims to describe the use of drugs in patients with Schizophrenia in the inpatient installation at Dr. Soeharto Heerdjan Mental Hospital. The method used was a descriptive study of schizophrenia patients. The study population was patients of Dr. Soeharto Heerdjan Mental Hospital in the period October-December 2021. Total sampling with inclusion criteria was used from medical record data. The authors obtained 692 samples. The data is displayed in the form of a frequency distribution table. The results obtained were 69.83% male and 30.17% female; the youngest patient was 17 years old, and the oldest patient was 79 years old. The authors obtained 1765 prescriptions from single prescriptions to 54 drug combination prescriptions. Drug administration for Schizophrenia is the right patient, diagnosis, and frequency of drug administration, but still found 5.22% inappropriate drug administration and 5.22% inappropriate process. Overall, the rational use of drugs at Dr. Soeharto Heerdjan Mental Hospital is still within the limits of the rational drug use module issued by the Ministry of Health in 2011. However, there needs to be improvement (quality control) at the institution for drug therapy and dosage in schizophrenia patients because there are still cases of drug dose combinations that exceed the maximum dose when compared to drug rationality guidelines based on the Pharmacotherapy Handbook Ninth Edition Algorithms.